Perbandingan Efektivitas Antara Kelompok Siswa yang Menggunakan Metode Pembelajaran TaRL & Menggunakan Metode Pembelajaran CRT - Natania Amanda (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is a quantitative research with a quasi-experimental research design. Comparison of the effectiveness between groups of students using the TaRL (Teaching at The Right Level) learning method as a control group and groups of students using the CRT (Culturally Responsive Teaching) learning method as an experimental group on the Mathematics Learning Outcomes of Students IX MIPA 1 and IX MIPA 2 SMAS Mardi Yuana Bogor Regency. The sampling technique was carried out by determining according to the wishes of the researcher, namely students who were already in the class. The instrument used in this study was in the form of a test in the form of pretest and posttest questions to measure student learning outcomes. The instruments tested amounted to 20 questions with an objective or multiple-choice test assessment system which were analyzed using simple regression analysis including the t-test and coefficient of determination. The results of the study showed that there was no significant difference between the group of students using the TARL (teaching at the right level) learning method and the group of students using the CRT (culturally responsive teaching) learning method on mathematics learning outcomes as indicated by t count < t table (1.04 < 2.021) and a significance value of 1.04 > 2.024.